Commentators View on Medicinal Plants of Sushrutokta Salsaradi Gana Regarding their Controversial Botanical Identity: A Review (International Journal of Ayurveda and Pharma Research, 2023)
Sushruta Samhita is one of the foundational literature included in the Brihat traiye literatures of Ayurveda. Out of 37 different Ganas mentioned in Sutra Sthana of Sushruta Samhita, Dravya-sangrahaniya-adhyaya; Salsaradi-gana is one of them in which 23 medicinal plants have been described.  Classically Salsaradi-gana is clinically indicated for Kushta (skin diseases), Prameha (diabetes mellitus), Pandu (anemia), and Kapha-medo-vishoshana (anti-hyperlipidaemic) disease. For this study, a review of the original commentary of Acharya Dalhana and Acharya haranchandra on Sushruta Samhita and the scientific research papers published on the medicinal plants listed in the Salsaradi-gana of Sushruta Samhita in indexed journals is done. Out of 23 medicinal plants mentioned 8 plants have controversial identification. The controversy in the identification of these medicinal plants is seen directly affecting the pharmacological action and clinical efficacy. Those 8 plants’ controversial identity is cleared with the establishment of a genuine plant for each of the plants through scientific and classical justification.